Некоторые вопросы русской аспектологии и словообразование - Галнайтите, Э. (Kalbotyra, 1986)
Considering word-formation as a special part of linguistics and interpreting the category of aspect as a lexico-grammatical one makes it necessary to revise some problems of Russian aspectology, such as Aktionsart and derivational types, aspect correlations, etc.